The Practice of Distance Education Orientation on Tccs - Primo, Lane; Ribeiro de Oliveira e Silva, Cassandra (Revista Brasileira de Aprendizagem Aberta e a Distância, 2018)
In distance education, the student is followed, accompanied by an instructor, who undertakes several roles and functions. On the case of this research, it is shown an evaluation of distance orientation practice for Course Conclusion Work (TCC, acronym in Portuguese) from two classes of distance learning latu sensu specialization courses, by Senac-CE. Even with positive results, there were problems during the phase of orientation on elaboration of TCCs, which provoked a work overload and stress for both students and instructors. Aiming to implement better practices to the next classes, this research was developed and reached its highest with recommendations for distance orientation practices for TCCs elaboration. Part of these recommendations have already been applied in three new classes, with positive outcomes for both students and instructors.